Collaborative Management in Ecotourism Business: Evidence from Perum Perhutani and Guci Ashafana Partnership - Dwi Puspita, Alfiyah; Irsyadul Ibad (PT. Sangadji Media Publishing, 2025)
Purpose – This study aims to examine the collaboration between Perhutani KPH Pekalongan Barat and Guci Ashafana in the development of state forest-based ecotourism. The research is grounded in Perhutani’s 2024 strategic objective to empower subsidiaries through business spin-offs. This study seeks to contribute to the understanding of collaborative governance practices in the context of sustainable tourism development, particularly by analyzing how theoretical principles of collaboration are operationalized in practice. Design/method/approach – A qualitative descriptive approach was employed to explore the collaboration process. Data were collected through interviews, document analysis, and direct observation. The analysis was guided by the collaborative governance framework developed by Ansell and Gash, focusing on elements such as dialogue, trust, commitment, shared understanding, and intermediate outcomes. Findings – The findings reveal that the collaboration was grounded in intensive face-to-face dialogues, transparent communication, and mutual commitment. Trust between Perhutani and Guci Ashafana was built through consistent actions and fulfillment of agreed responsibilities. The cooperation agreement reflected a shared understanding that integrated economic, ecological, and social goals. The collaboration resulted in tangible community empowerment through job creation, increased local economic involvement, and environmental conservation initiatives. Implications – The results demonstrate how collaborative governance can be effectively implemented in state-owned enterprise initiatives, offering practical insights for policymakers and practitioners seeking to develop community-based tourism within forest areas. It also highlights the importance of aligning institutional objectives with community needs. Novelty/Originality – This research provides a rare empirical example of successful collaboration between a state-owned enterprise and a local tourism operator in Indonesia, applying the collaborative governance model to a real-world ecotourism project. The study contributes to the limited body of literature on SOE-led sustainable tourism partnerships in Southeast Asia.